Spatial utilization in informal settlements - Gonzaga, Gemma Sheila C.; Lejarde, Godesil G.; Santos, Romeo B. (2005)
This paper looked into the nature of spatial utilization in informal settlements. A survey of two informal housing settlements with contrasting locations was conducted to determine the way space is "utilized" in relation to the geographical and demographic characteristics of the localities. Preliminary results of this initial study show that considerable differences indeed are manifested, althogether obvious though, coming as it should from the effects of geographic & economic factors involved. But the inforal settlers' utilization of the spatial elements of the house shoes a number of things more. Among others, it points to a common tendency among informal settlers to rationalize and to rise above geographic and demographic limitations, such that the resultant spaces being created are manifestations of an attempt to privacy, organization and utility -however crude these might be.
Keywords: Informal settlements -- Baguio City; Informal settlements -- Lapulapu City (Cebu)